Are preoperative acute phase proteins serum levels associated with clinical outcome in non-small cell lung cancer patients? - Kasprzyk, Mariusz; Dyszkiewicz, Wojciech; Roszak, Magdalena; Gabryel, Piotr; Gałęcki, Bartłomiej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background : Each malignant neoplasm can lead towards the initiation of the acute phase reaction. A special form of the acute phase reaction is the coordinated synthesis of several proteins. Quantitative acute phase protein (APP) changes observed during the neoplastic process remain unclear. They can result from the development of immunosuppression connected with the production of immunosuppressive cytokines by the tumor. The research on the role of cytokines and acute phase proteins as prognostic factors, following surgical management of malignant tumors is scarce, and the results are ambiguous. Aim : The aim of the study was to assess the quantitive changes of the APP serum level in patients with non small cell lung cancer (NSCLC), who underwent a radical resection. We analysed the correlations between the quantitive changes of APP and: age, gender, the histological type of cancer, T stage, N stage and grading. Material and methods : We analysed a group of 192 patients surgically treated for NSCLC from 2008 to 2009. The study group consisted of 144 male and 48 female patients, aged between 38 and 79 years (average: 62.9 yrs). The most frequent histological types of cancer were: the squamous cell lung cancer (88 patients) and the adenocarcinoma (71 patients). The majority of them were in stage I B (52 patients) and III A (39 patients). We analysed serum levels of: C-reactive protein (CRP), alfa 1 acid glicoprotein (AGP), alfa 1 antitrypsin (AT), and haptoglobin (Hp) using the method of rocket immunoelectroforesis by Laurell. Statistical analysis was based on the Statistica 8.0 software. Results : We didn’t find any significant differences between APP levels and age, but all APP levels were significantly higher in male patients. The CRP and AT levels correlated with grading and were higher in G2 and G3 tumors. The serum levels of CRP and Hp were significantly higher in patients with squamous cell lung cancer compared to other histological types. The levels all of four APP were significantly higher in the group of patients with T3 or T4 category, while the patients with N1 or N2 status had significantly higher concentrations of CRP and Hp. We observed a positive correlation between serum levels all of APP and TNM stage. Conclusions : The serum concentration of selected APP may correlate with more aggressive clinical behaviour of lung cancer. The patients with N1 or N2 stage of the squamous cell lung cancer have significantly higher serum level of CRP and Hp. The preoperative concentration all of APP correlates with TNM stage. These proteins could serve as prognostic factors in the risk assessment of the cancer recurrence after the surgical management.